KESULITAN BELAJAR MATEMATIKA (STUDI KASUS) PESERTA DIDIK KELAS IV MADRASAH IBTIDAIYAH AL-FITRAH UMI KOTA MAKASSAR - Hilwa Tenriola, Andi; Syahid, Akhmad; Wakka, Ahmad; Martini; Aidil Sudamono R, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the mathematics learning process for fourth-grade students at Madrasah Ibtidaiyah Al-Fitrah UMI, identify the types of learning difficulties experienced by students in long multiplication and long division materials, and analyze the factors causing these learning difficulties. This research employed a qualitative method with a descriptive approach. The subjects of this study were the fourth-grade mathematics teacher and students at Madrasah Ibtidaiyah Al-Fitrah UMI. Data were collected through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results showed that mathematics learning in the fourth grade followed the Kurikulum Merdeka using lecture methods and practice exercises. The identified learning difficulties included a low understanding of long-form arithmetic operations, evidenced by the majority of students scoring below the Minimum Mastery Criterion (KKM) during assessments. Students faced obstacles in calculating large numbers and frequently felt confused by the steps of long division. The causal factors for these learning difficulties consisted of internal and external factors: 1) The teacher's teaching method, which tended to be monotonous, thereby decreasing student motivation and concentration; 2) Students' limited cognitive abilities in mastering basic arithmetic concepts; and 3) A lack of learning assistance from parents at home, which resulted in students having difficulty reviewing the material in-dependently. Keywords: Learning Difficulties, Mathematics, Long Multiplication and Division,